Survey data for birds, bryophytes, lichens and vascular plants from 40 Scots pine and Norway spruce stands in southern Sweden - Petersson, Lisa; Lariviere, Delphine; Holmström, Emma; Lindbladh, Matts; Felton, Adam (Swedish University of Agricultural Sciences, 2023)
The aim of the data collection was to examine differences in biodiversity between two different age classes of production forest stands. Surveys were conducted between 2016-2017 in forty managed production forest stands in southern Sweden. Stands are dominated by two different tree species: Scots pine and Norway spruce and belong to two different age classes: 55 (+/- 5) and 80 (+/- 5) year old. In total ten stands of each category (tree species and age class) were surveyed. There are four separate data sets for species: birds, bryophytes, epiphytic lichens and vascular plants. Species data consists of presence/absence data for the different stands. There is also one data set with stand structures. The five different data sets can be connected using a stand ID that can be found in all of the files. Data consists of information about 26 bird species, 84 bryophyte species, 57 lichen species and 102 vascular plant species.

Files consist of 5 separate matrices with 40 rows that are stored in .csv format (comma delimited). Data set 'bird.csv' has 40 rows and 29 columns. Data set 'bryophyte.csv' has 40 rows and 87 columns. Data set 'epilichen.csv' has 40 rows and 60 columns. Data set 'vascularpl.csv' has 40 rows and 105 columns. Data set 'stand_structures.csv' has 40 rows and 7 columns. All data sets have a column "stand", which consist of stand IDs which can be used to connect the different data sets with each other. Information about tree species and stand age class is also provided in the data. For bird species common English names are used. Scientific names are used for vascular plants (Dyntaxa 2019), bryophytes (Hallingbäck 2006) och lichens (Santesson's Checklist of Fennoscandian Lichen-forming and Lichenicolous Fungi 2020).

Data was collected during summer of 2016 (birds, bryophytes, vascular plants and forest structure data) and during summer of 2017 (lichen data and forest structure data). Data consist of information from fourty stands. In each stand, 10 plots of 100m2 were used for inventoring bryophytes and vascular plants and 10 trees were surveyed for epiphytic lichens (including branches, up to two metres). Birds were surveyed in four plots per stand within a radius of 40 meters. In the data sets, absence-presence data for the whole stand is shown (i.e. when pooling all plots/trees together). Forest structures were measured within a radius of 10-15 meters in 10 plots per stand, except for dead wood, which was measured in 100 m2 plots. The data set 'stand_structures' shows hectare values based on the average from the plots. Column name explaination: 'stand' = stand-ID, 'tree' = tree species, 'age' = stand age, 'basal_area' = basal area, 'stem_density' = stem densities (stems > 4 cm diameter) and 'wood' = dead wood in m3 (snags, lying wood). The column 'canopy_cover' shows the average canopy cover calculated from 10 hemispherical photos per stand.

Stands were selected based on site index (SI 24-29 for Norway spruce) from forest owner management plans. Only stands on till soil with rhyolite or granite bedrock were selected for the study.

For details about study design, species inventories and stand selection see following publications:

*Birds*
Lindbladh M, Petersson L, Hedwall P-O, Trubins R, Holmström E, Felton A. Consequences for bird diversity from a decrease in a foundation species—replacing Scots pine stands with Norway spruce in southern Sweden. Regional Environmental Change. 2019;19(5):1429-40. doi: 10.1007/s10113-019-01480-0.

*Bryophytes*
Petersson L, Nilsson S, Holmström E, Lindbladh M, Felton A. Forest floor bryophyte and lichen diversity in Scots pine and Norway spruce production forests. Forest Ecology and Management. 2021;493:119210. doi: 10.1016/j.foreco.2021.119210. PubMed PMID: WOS:000651205800009.

*Epiphytic lichens*
Petersson L, Lariviere D, Holmström E, Fritz Ö, Felton A. Conifer tree species and age as drivers of epiphytic lichen communities in northern European production forests. The Lichenologist. 2022;54(3-4):213-25. Epub 2022/07/29. doi: 10.1017/S0024282922000172.

*Vascular plants*
Petersson L, Holmström E, Lindbladh M, Felton A. Tree species impact on understory vegetation: Vascular plant communities of Scots pine and Norway spruce managed stands in northern Europe. Forest Ecology and Management. 2019;448:330-45.

Syftet med datainsamlingen var att undersöka skillnader i biologisk mångfald mellan två olika ålderskategorier av produktionsskogsbestånd. Inventeringarna ufördes mellan 2016-2017 i fyrtio brukade produktionsbestånd i södra Sverige. Bestånden domineras av två olika träslag: tall och gran och tillhör två olika ålderskategorier: 55 (+/- 5) och 80 (+/- 5) år. Totalt finns inventerad data för tio bestånd av varje kategori (trädslag och ålderskategori). Det finns fyra olika dataset med artdata: fåglar, mossor, epifytiska lavar och kärlväxter. Det finns också ett dataset med beståndsstrukturer. De fem dataseten kan analyseras tillsammans genom att använda ett gemensamt bestånds ID som finns i alla filer.
Data består av befintlighetsdata (1/0) för de olika bestånden. Totalt innehåller dataseten uppgifter om 26 fågelarter, 84 mossarter, 57 lavarter och 102 kärlväxtarter.

Filerna består av 5 separata datamatriser i .csv-format (kommaseparerad). Dataset 'bird.csv' har 40 rader och 29 kolumner. Dataset 'bryophyte.csv' har 40 rader och 87 kolumner. Dataset 'epilichen.csv' har 40 rader och 60 kolumner. Dataset 'vascularpl.csv' har 40 rader och 105 kolumner. Dataset 'stand_structures.csv' har 40 rader och 7 kolumner.
Alla data set har en kolumn som heter "stand" och som innehåller bestånds-ID. Dessa kan användas för att koppla ihop de olika datamatriserna. Information om träslag och ålderskategori finns också i datat. Engelska artnamn används till fåglarna. Vetenskapliga namn används för kärlväxter (Dyntaxa 2019), mossor (Hallingbäck 2006) och lavar (Santesson's Checklist of Fennoscandian Lichen-forming and Lichenicolous Fungi 2020).

Data samlades in under sommaren 2016 (fåglar, mossor, kärlväxter och skogsdata) och under sommaren 2017 (lavar och skogsdata). Datat innehåller information från fyrtio bestånd. I varje bestånd inventerades mossor och kärlväxter i 10 provytor som var 100m2 stora och tio träd inventerades på lavar (inklusive grenar, upp till 2 m). Fåglar inventerades i fyra provytor per bestånd. Provytornas radie var 40 meter. Förekomst data (1/0) för hela beståndet visas i data setet (alltså vilka arter som hittats i beståndet när alla ytor/träd lagts samman). SKogliga strukturer mättes in i ytor inom 10-15 m radie i tio ytor per bestånd, förutom död ved som mättes in i 100 m2 stora ytor. Datasetet 'stand_structures' visar hektarvärden baserat på medelvärde från de tio ytorna/bestånd. Kolumnnamnens betydelser: 'stand' = bestånds-ID, 'tree' = trädslag, 'age' = beståndsålder, 'basal_area' = grundyta, 'stem_density' = stamantal (stammar > 4 cm diameter) och 'wood' = död ved i m3 (stående, liggande). Kolumnen 'canopy_cover' visar krontäckningens medelvärde beräknat på 10 hemisfäriska foton per bestånd.

Stands were selected based on site index (SI 24-29 for Norway spruce) from forest owner management plans. Only stands on till soil with rhyolite or granite bedrock were selected for the study.

Mer detaljer om metod, artinventeringar och beståndsurval finns i följande artiklar:


*Fåglar*
Lindbladh M, Petersson L, Hedwall P-O, Trubins R, Holmström E, Felton A. Consequences for bird diversity from a decrease in a foundation species—replacing Scots pine stands with Norway spruce in southern Sweden. Regional Environmental Change. 2019;19(5):1429-40. doi: 10.1007/s10113-019-01480-0.

*Mossor*
Petersson L, Nilsson S, Holmström E, Lindbladh M, Felton A. Forest floor bryophyte and lichen diversity in Scots pine and Norway spruce production forests. Forest Ecology and Management. 2021;493:119210. doi: 10.1016/j.foreco.2021.119210. PubMed PMID: WOS:000651205800009.

*Lavar*
Petersson L, Lariviere D, Holmström E, Fritz Ö, Felton A. Conifer tree species and age as drivers of epiphytic lichen communities in northern European production forests. The Lichenologist. 2022;54(3-4):213-25. Epub 2022/07/29. doi: 10.1017/S0024282922000172.

*Kärlväxter*
Petersson L, Holmström E, Lindbladh M, Felton A. Tree species impact on understory vegetation: Vascular plant communities of Scots pine and Norway spruce managed stands in northern Europe. Forest Ecology and Management. 2019;448:330-45.
Inventeringsdata för fåglar, mossor, lavar och kärlväxter från 40 tall- och granbestånd i Sydsverige
Data used for the study: The potential implications of shortened rotation length for forest birds, bryophytes, lichens and vascular plants: Example from southern Swedish production forests
Keywords: vascular plants; mosses; liverworts; biodiversity; biologisk mångfald; lichens; bryophytes presence; survey; birds; forest management; skogshantering; Lecanoromycetes; Bryophyta; bladmossor; Aves; fåglar; Tracheophyta; kärlväxter; Natural Sciences; Naturvetenskap; Ecology; Ekologi; Forest Science; Skogsvetenskap; Environmental Sciences and Nature Conservation; Miljö- och naturvårdsvetenskap